Model of security threats for wireless communication systems in millimeter wave range - Salnykov, D.; Tsopa , O. (Radiotekhnika, 2018)
The article is devoted to the problem of using the next generation 5G, mil-lime waves (MM DV) in wireless communication systems. Possessing a high directivity and being susceptible to blocking by environmental objects, MM channels are often considered difficult to intercept by an intruder. The purpose of the work is to develop a threat model for the MM DL channel and to assess the security of the wireless data transmission system with the OC. A common threat model for evaluating the security parameters of information transmission systems at the physical level using a millimeter wave band (MM DV) is obtained.